Uso didático de telefones celulares na educação de jovens e adultos : uma proposta para elaboração de reportagens em vídeo por discentes - Nascimento, Rosangela Dias Carvalho do (2023)
This investigation starts from the research problem identified in Youth and Adult Education (EJA), which refers to the presentation of unattractive classes, with insufficient use of Digital Information and Communication Technology (TDIC). In addition, there are gaps that refer to the non-identification of a specific teaching method for EJA, as well as the scarcity of research relating this teaching modality with TDIC. Thus, the work contributes epistemologically by describing a teaching method that guides teachers regarding the didactic use of cell phones for the elaboration of video news reportages made by EJA students. The described method transits through active methodological issues, which concern dialogue, participation and collaboration among students of this teaching modality, considering existing interfaces between Computing, Communication and Education. The epistemological basis of the investigation is Design Science and the method that operationalizes it is Design Science Research.